2022
DOI: 10.21608/jcbr.2022.168085.1280
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal and cerebellar anti-toxic effects of curcumin against orlistat associated toxicity in obese male albino rats

Abstract: Background: Orlistat is one of the common medicines in treating overweight, and its use may cause several side effects. Curcumin, a yellow phenolic compound isolated from Curcuma longa's rhizome, possesses several pharmaceutical effects due to its antioxidant and anti-inflammatory properties. Aim: This work aimed to test the possible protective effect of curcumin against orlistat-induced hepatorenal and cerebellar toxicities in obese albino rats. Material and Methods: Forty adult male albino rats were equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, in vivo animal studies have indicated that orlistat can lead to intestinal villi damage [19] and hepatotoxicity [20]. Moreover, there have been connections between orlistat use and the development of neurodegenerative disorders [21]. Close monitoring and appropriate patient education regarding potential side effects are essential to ensure the safe use of orlistat in children.…”
Section: Orlistatmentioning
confidence: 99%
“…However, in vivo animal studies have indicated that orlistat can lead to intestinal villi damage [19] and hepatotoxicity [20]. Moreover, there have been connections between orlistat use and the development of neurodegenerative disorders [21]. Close monitoring and appropriate patient education regarding potential side effects are essential to ensure the safe use of orlistat in children.…”
Section: Orlistatmentioning
confidence: 99%